The Genes of CYP, ZEP, and CCD1/4 Play an Important Role in Controlling Carotenoid and Aroma Volatile Apocarotenoid Accumulation of Apricot Fruit - Xi, Wanpeng; Zhang, Lina; Liu, Shengyu; Zhao, Guohua (Frontiers in Plant Science, 2020)
Carotenoids are important coloration molecules and indispensable component of the human diet. And these compounds confer most of the apricot fruit yellow or orange color. In China, fruit of some apricot cultivar present light-yellow color but strong flowery flavor, however, the chemical mechanism remains unknown. Here, carotenoids and aroma volatile apocarotenoids (AVAs) in three skin types of apricot cultivars (orange, yellow and light-yellow skinned) were determined by HPLC and GC-MS, respectively. And the transcript levels of carotenogenic genes were analyzed by qRT-PCR. The orange-skinned cultivars ‘Hongyu’ and ‘Danxing’ fruit presented the most abundant total carotenoid, β-carotene and specific α-carotene contents, and β-carotene (52% - 77%) increased to become the dominant carotenoid during fruit ripening. The transcript levels of lycopene β-cyclase (LCYb) and β-carotene hydroxylase (CHYb) sharply increased during ripening. The yellow-skinned cultivars ‘Sulian No. 2’ and ‘Akeyaleke’ fruit contained lower levels of total carotenoids and β-carotene but were rich in phytoene. The light-yellow coloration of ‘Baixing’ and ‘Luntaixiaobaixing’ fruit was attributed to low amounts of total carotenoids, lutein, and neoxanthin and an absence of β-cryptoxanthin, but high level of aroma volatile apocarotenoids (AVAs) such as β-ionone were detected in these cultivars fruit, accompanied by low transcript levels of carotenehydroxylase (CYP) and zeaxanthin epoxidase (ZEP) but high levels of carotenoid cleavage dioxygenase 1 (CCD1) and CCD4. Correlation analysis showed that the expression level of CCD1 negatively correlated with carotenoid accumulation but positively with AVAs production. These collected results suggest that both carotenoid biosynthesis and degradation are important for apricot coloration and aroma formation. CYP, ZEP, CCD1 and CCD4 may be the key regulation points for carotenoid and AVAs accumulation in apricot fruit, which provide important targets for quality-oriented molecular breeding.